Kematangan Karir Mahasiswa Jurusan Tarbiyah Sekolah Tinggi Agama Islam Negeri (STAIN) Samarinda - Malik, Lina Revilla (FENOMENA, 2015)
The objective of this study was to describe the level of career readiness of the education faculty students of STAIN Samarinda and the aspects of career readiness of the education faculty students of STAIN Samarinda. The sample of this study was 92 students of the education faculty students. The researcher used stratified random sampling in this study. The data were collected by using questionnaires. The data were analized through rating scale. The result of findings shows that the level of career readiness of the education faculty students of STAIN Samarinda was 73% with 17.156 interval or it is categorized as âGoodâ. It is affected by the ages of the respondents in the age of 18 â 25 years old which means they are in the sub level of transition and trial little commitment. It is also affected by the factors of interest, skill, and personality. The aspects of career readiness of the education faculty students of STAIN Samarinda are as follows: 1) Career planning is 73.12%, categorized as âGoodâ. It is affected by the respondentsâ knowledge of workfield, interest, education, extra-curricular activities, and spare-times activities. 2) Career exploration is 68.7%, categorized as âGoodâ. It is affected by the respondentsâ family background and social life interaction. 3) Career decision is 76.3%, categorized as âGoodâ. It is affected by the respondentsâ social economical background. 4) Work-field information is 73.5%, categorized as âGoodâ. It is affected by the educational and economical background of the respondentsâ parents.